Experimenting with policy design: fostering reshoring in Emilia Romagna region - Clio Dosi; Matteo Vignoli; Paolo Barbieri; Federico Frattini; Franco Mosconi; Giorgio Prodi (CERN IdeaSquare Journal of Experimental Innovation, 2022)
Design for policy deals with the policy cycle by recurring to design practices and tools, such as user-centered design, co-design, insights identification, abduction, creativity, prototyping. Empirical studies show that practice of design as inspirational and creative practice usually happens in the first phases of the policy cycle, and it hardly manages the challenges faced in policy formulation and policy implementation of the later phases of the policy cycle. In this case study we experiment with a policy innovation process that deals with those practices also in later stages of the policy cycle. The case study settles at the Regional level in Emilia Romagna to foster Reshoring initiatives.